2015
DOI: 10.1002/cncr.29256
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and risk of pancreatic cancer: Results from a large, clinic‐based case‐control study

Abstract: Background Statins are cholesterol-lowering medications with pleiotropic effects including alterations in growth signaling as well as immunomodulatory and anti-inflammatory effects that may alter cancer risk. Evidence from previous epidemiologic studies is inconsistent regarding whether statin use is associated with reduced risk of pancreatic cancer (PC). Methods Patients with confirmed diagnoses of PC (cases) were recruited from medical and surgical oncology clinics, with controls (frequency-matched by sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…Furthermore, in a matched case-control study, male smokers who were regular statin users had a significantly reduced OR for pancreatic cancer (42). In a large case-control study (1,405 participants), statin use in men (OR, 0.50; 95% CI, 0.32-0.79) and a duration of statin use of >10 years (OR, 0.51; 95% CI, 0.31-0.85) were significantly associated with a reduced risk of pancreatic cancer (43).…”
Section: Statins and Pancreatic Cancermentioning
confidence: 97%
“…Furthermore, in a matched case-control study, male smokers who were regular statin users had a significantly reduced OR for pancreatic cancer (42). In a large case-control study (1,405 participants), statin use in men (OR, 0.50; 95% CI, 0.32-0.79) and a duration of statin use of >10 years (OR, 0.51; 95% CI, 0.31-0.85) were significantly associated with a reduced risk of pancreatic cancer (43).…”
Section: Statins and Pancreatic Cancermentioning
confidence: 97%
“…They found that the use of simvastatin and atorvastatin after cancer diagnosis is associated with longer survival in patients with non-metastatic pancreatic adenocarcinoma. Walker et al (2015) observed associations in men only, and PC risk was inversely related to the duration of statin use. Interestingly, results from meta-analyses of randomized controlled trial data show that statins may reduce the risk of acute pancreatitis and increase diabetes risk (Desai et al 2014), and these conditions are associated with increased PC risk (Walker et al 2015).…”
Section: Effect Of Statins In Animal and Human Studiesmentioning
confidence: 75%
“…Walker et al (2015) observed associations in men only, and PC risk was inversely related to the duration of statin use. Interestingly, results from meta-analyses of randomized controlled trial data show that statins may reduce the risk of acute pancreatitis and increase diabetes risk (Desai et al 2014), and these conditions are associated with increased PC risk (Walker et al 2015). Simvastatin increased survival of pancreatic cancer patients more potently than the other statins .…”
Section: Effect Of Statins In Animal and Human Studiesmentioning
confidence: 75%
See 1 more Smart Citation
“…12 One clinical-based casecontrol study in 2015 implied that risk reduction of pancreatic cancer in stain users may be apparent particularly in specific groups, such as in men and long-term users. 13 Diabetic patients have a greater likelihood of underlying hyperlipidemia 14 and a higher risk of cardiovascular disease, 15 which is leading to the stricter control of cholesterol levels. 16 Diabetic patients may use more statins compared to nondiabetic subjects and tend to have a higher risk of developing pancreatic cancer.…”
mentioning
confidence: 99%